Effect of auriculotherapy on anxiety-fatigue and sleep disturbances in cancer patients: A scoping review - Silmara de Oliveira Silva; Vinicius dos Santos Lemos Pereira; Mariane Elivânia Silva; Jucielly Ferreira da Fonseca; Maria Carolina Batista da Silva; Roberta Paolli de Paiva Oliveira Arruda Camara; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas (Complementary Therapies in Medicine)
Objective: This study aims to map the scientific literature on the effects of auriculotherapy in the treatment of anxiety-fatigue and sleep disturbances in cancer patients, highlighting the main application protocols. Method: A scoping review was conducted following the PRISMA-ScR guidelines and the Joanna Briggs Institute methodology. The search was conducted in twelve data sources by two independent researchers. Publications were included if they were available in full text, with no language or time restrictions. Data were analyzed descriptively, with tables and statistics reporting absolute and relative frequencies. Results: The final sample included 16 studies with a total of 669 cancer patients. Of these, 11 were randomized controlled trials published between 2015 and 2022, with a notable concentration in 2019 and 2021. Asian countries were highly represented (62,5 %), followed by Latin America (12,5 %). Breast cancer was the most common tumor type, accounting for 68,75 %. The primary auricular points used were shenmen, followed by heart, subcortex, kidney, and sympathetic. The duration of the protocols ranged from three to eight weeks. The most commonly used materials were needles, seeds, magnetic pellets, and crystal balls. Conclusions: The results of this review highlight the effects of auriculotherapy in the management of anxiety-fatigue and sleep disturbance in cancer patients, demonstrating symptom improvement and benefits that outweigh the minor side effects associated with the procedure.